DevSecOps metrics - Prates, L.; Faustino, J; Silva, M.; Pereira, R. (Information Systems: Research, Development, Applications, Education. Lecture Notes in Business Information Processing, 2019)
DevSecOps is an emerging paradigm that breaks the Security Team Silo into the DevOps Methodology and adds security practices to the Software Development Cycle (SDL). Security practices in SDL are important to avoid data breaches, guarantee compliance with the law and is an obligation to protect customers data. This study aims to identify metrics teams can use to measure the effectiveness of DevSecOps methodology implementation inside organizations. To that end, we performed a Multivocal Literature Review (MLR), where we reviewed a selection of grey literature. Several metrics purposed by professionals to monitor DevSecOps were identified and listed.